Student And Teacher Perceptions Of Extensive Reading Practice - Yeni Suryani; Siminto (Gudang Jurnal Multidisiplin Ilmu, 2023)
Extensive reading practice is a reading activity that involves a variety of materials outside the official curriculum. This research aims to understand how students and teachers implement Extensive Reading Practice and its impact on language learning. The research method used is a literature review, in which information is collected and analyzed from various sources such as journal articles, books, and related references. The results showed that Extensive Reading Practice received positive responses from students and teachers. Students reported improved reading skills, increased vocabulary, better text comprehension, and increased interest in reading. Meanwhile, teachers reported that extensive reading practice increased students' motivation to learn and active participation in language learning. The role of the school in providing adequate resources for extensive reading practice is also very important. This includes a well-stocked library and a variety of reading materials to support different reading activities. Overall, this study shows that extensive reading practice has significant benefits for students and teachers in improving language proficiency and motivation to learn.